Sanitary Assurance at Biosolids Composting Facilities: Assessing the Efficiency of Temperature-Contact Time Criterion. Issue 3 (3rd July 2019) - Isobaev, Pulat; Wichuk, Kristine; McCartney, Daryl; Neumann, Norman F.
Abstract: Pathogen inactivation due to temperature exposure was studied in full-scale covered aerated static piles (CASP) treating municipal biosolids. The objectives of the study were to assess the impact of the temperature contact time on pathogen inactivation and to analyze whether the gradual increase in temperature, as occurs in compost piles, trigger a viable-but-non-culturable (VBNC) state. Twenty-two temperature probes imitating random particle behavior were seeded with Escherichia coli and Salmonella and introduced into the CASP. It was found that 92% of the compost pile experienced temperatures ≥55 °C for at least three consecutive days during the first stage of composting (36 days). This number rose to 93% after the pile was turned and composted for a further 20 days. At the end of active composting, the fecal coliforms level in the compost matrix, determined by culturing methods, was <10 3 MPN·g −1 total solids, while Salmonella was below its detection limit of <3 MPN·4 g −1 total solids. The molecular method indicated that there were live cells which had apparently entered a VBNC state. Nonetheless, it was concluded further study is needed to assess overall risk, since other factors such as pH, toxic compounds, and microbial competition and antagonism were excluded from this particular study. In future, as the techniques presented herein are refined, they may be useful for validating different types of composting technologies for sanitation effectiveness.